Migración y vida cotidiana: nueva mirada en el contexto Estados Unidos-Cuba, 2017-2019 / Migration and daily life: a new look in the context of US-Cuba, 2017-2019 - Consuelo Martín Fernández; Jany Bárcenas Alfonso; Arlene Lucía Cruz Guevara (Universidad de La Habana, 2020)
The relationship between daily life and migration offers a new vision of the current context of US restrictive migratory policy towards Cuba, 2017-2019. The study focuses on the perceptions about the changes in US migration policy towards Cuba, and the psychosocial impact of these changes on Cuban daily life. The mixed methodology with a sequential design is used, 150 people in the quantitative phase, and 20 case studies in the qualitative phase. Discussion of results: In 2017, there existed a low perception of the effects of the migratory restrictions on Cuban daily life, because of limited knowledge about the restrictive measures. The term credible fear is unknown for the great majority of the people. They are waiting passively for the elimination of the restrictions with the arrival of a new president to the US government. In 2019, there is extensive knowledge of the restrictive migratory policy towards Cuba; they are mostly rejected and are associated with negative emotions, symbolically centered on the figure of Trump. The family constitutes the principal sphere of daily life that receives the largest impacts. Family reunification is limited due to high financial costs, and migratory projects must wait for the return of a policy of normalization of migratory relations. The changes in the US migration policy are not recognized as part of the changes that take place in current Cuban daily life. The issue of migration has been and is very important for Cuba, in defense of family ties between the nation and its emigrants. Resumen La relación entre vida cotidiana y migración ofrece una nueva mirada al actual contexto de la política migratoria restrictiva de Estados Unidos hacia Cuba, 2017-2019. El estudio se enfoca en las percepciones sobre los cambios en la política migratoria estadounidense hacia Cuba y el impacto psicosocial de esos cambios en la vida cotidiana cubana. Se emplea una metodología mixta con diseño secuencial, 150 sujetos en la etapa cuantitativa y 20 estudios de caso en la etapa cualitativa. Discusión de resultados: En 2017 existe una baja percepción de los efectos de las restricciones migratorias en la vida cotidiana cubana, debido a un escaso conocimiento de estas medidas. El término miedo insuperable es desconocido por la gran mayoría de los sujetos. Se espera de forma pasiva la eliminación de las restricciones con la llegada de un nuevo presidente al Gobierno de Estados Unidos. En 2019 existe amplio conocimiento sobre la política migratoria restrictiva hacia Cuba; predomina rechazo hacia esa política y se asocia a emociones negativas, centradas simbólicamente en la figura de Trump. La familia constituye la principal esfera de la vida cotidiana que recibe mayores impactos, se ve limitada la reunificación familiar por altos costos económicos y proyectos migratorios esperan que se retome una política de normalización de relaciones migratorias. Los cambios de la política migratoria estadounidense no se reconocen como parte de los cambios que tienen lugar en la vida cotidiana cubana actual. El tema migratorio ha sido y es muy importante para Cuba, en defensa de vínculos familiares entre la nación y su emigración.